Personality traits and psychological well-being among undergraduate students at selected public university in Kuala Lumpur - Gimhani, Sachindra; Ismail, Nik Ahmad Hisham; Abd Hamid, Siti Rafiah; Kassim, Siti Kholijah (Asian Scholars Network, 2025)
This study aims to investigate the relationship between personality traits and psychological well-being among undergraduate students at a selected public university in Kuala Lumpur. The study has three main objectives: (1) To identify the five personality traits based on Lewis Goldberg's OCEAN theory among the undergraduate students, (2) To determine the psychological well-being among the undergraduate students, (3) To examine the level of relationship between personality traits and psychological well-being of undergraduate students. This research employed a quantitative method, collecting data from 275 undergraduate students at a selected public university in Kuala Lumpur, using a random sampling technique. The data were analyzed using descriptive statistics namely mean scores and standard deviations, inferential statistics namely, Pearson Correlation Coefficients, independent sample t-tests, and ANOVA to address the research objectives and questions. The main findings revealed that conscientiousness and agreeableness positively influenced the undergraduates’ psychological well-being. The study recommends that students need to actively engage in self-regulation and utilize their personality strengths to enhance their psychological well-being